Impacts of tight multifactorial intervention in patients with type 2 diabetes: Implications from the Japan Diabetes Outcome Intervention Trial 3. Issue 5 (18th July 2018) - Araki, Eiichi; Senokuchi, Takafumi; Furukawa, Noboru
Abstract : Effects of intensive versus conventional therapy on the primary and secondary outcomes.